Determining the rational operating parameters for granite crushing to obtain cubiform crushed stone - Bozhyk, D. P.; Sokur, M. I.; Biletskyi, V. S. (Dnipro University of Technology, 2022)
Purpose. Determining the rational operating parameters for granite crushing under impact in the field of centrifugal forces to obtain cubiform crushed stone. In order to achieve the purpose set, the task is to determine the operating parameters for obtaining the main grain-size classes: -50.0 + 20.0; -40.0 + 20.0; -20.0 + 10.0; -10.0 + 5.0 and 5.0 mm. Methods. The crushing process of granite crushed stone is studied in the conditions of the Kolomoievskyi Granite Quarry, Dnipropetrovsk region. Granite crushed stone with an initial grain-size of 100.0-0.0 mm and strength grade of M1400 is subjected to crushing. The accelerating rotor rotation frequency is the design value n = 200-1200  min⁻¹. Fine crushing of granite is performed in a centrifugal-impact crusher by a free impact in the field of centrifugal forces. Findings. The optimal speed modes of centrifugal crusher operation, which provide the production of high-quality crushed stone with a maximum content of 90-95% cubiform fractions, have been substantiated. Originality. The yield dependences have been obtained of the grain-size classes: -50.0 + 20.0; -40.0 + 20.0; -20.0 + 10.0; -10.0 + 5.0 and 5.0 mm depending on the speed mode of the centrifugal crusher operation. Practical implications. The operating parameters for obtaining the main grain-size classes of cubiform crushed stone from granite have been determined: -50.0 + 20.0; -40.0 + 20.0; -20.0 + 10.0; -10.0 + 5.0 and 5.0 mm. In particular, it has been determined that for the production of cubiform crushed stone with -50.0 + 20.0 mm grain-size, the rotor rotation reasonable speed is 400-500  min⁻¹ (the speed of material departure from the accelerating rotor is 45-50 m/sec); for cubiform crushed stone of -40.0 + 20.0 mm grain-size, the speed mode is 200 min⁻¹ (25 m/sec); for cubiform crushed stone of -20.0 + 10.0 mm grain-size – 600-650 min⁻¹ (70-80 m/sec), respectively. The maximum content of cubiform fractions in the -20.0 + 10.0 mm grain-size class is 95%, which is achieved at a rotor speed of 650-700 min⁻¹ (departure speed is 75-80 m/sec). The maximum content of cubiform fractions in the -10.0 mm grain-size class is 94-95%, which is achieved at the accelerating rotor speed within 700-800 min⁻¹ (departure speed is 70-80 m/sec). The obtained data make it possible to practically choose a rational speed mode of the centri-fugal-impact crusher operation to obtain the maximum yield of cubiform crushed stone.

Мета. Визначення раціональних режимних параметрів дроблення граніту ударом в полі відцентрованих сил для одержання кубовидного щебню. Для досягнення поставленої мети поставлена задача встановити режимні параметри отримання основних класів крупності: -50.0 + 20.0; -40.0 + 20.0; -20.0 + 10.0 та -10.0 + 5.0 і 5.0 мм. Методика. Дослідження дроблення гранітного щебню проводились в умовах Коломоєвського гранітного кар’єру, Дніпропетровська область. Дробленню піддавали гранітний щебінь вихідної крупності 100-0 мм і маркою міцності М1400. Частота обертання розгінного ротора склала проєктну величину n = 200-1200 хв⁻¹. Дрібне дроблення граніту здійснювалося в дробарці відцентрово-ударного типу вільним ударом в полі відцентрових сил. Результати. Обґрунтовано оптимальні швидкісні режими роботи відцентрових дробарок, які забезпечують отримання високоякісного щебню з максимальним вмістом кубовидних фракцій 90-95%. Наукова новизна. Отримано залежності виходу класів крупності -50.0 + 20.0; -40.0 + 20.0; -20.0 + 10.0; -10.0 + 5.0 і 5.0 мм від швидкісного режиму роботи відцентрової дробарки. Практична значимість. Встановлено режимні параметри отримання основних класів крупності кубовидного щебню з граніту: -50.0 + 20.0; -40.0 + 20.0; -20.0 + 10.0; -10.0 + 5.0 і 5.0 мм. Зокрема, встановлено, що для виготовлення кубовидного щебню крупністю -50.0 + 20.0 мм обґрунтована швидкість обертання ротора – 400-500 хв⁻¹ (швидкість вильоту матеріалу з розгінного ротора 45-50 м/с); кубовидного щебню крупністю -40.0 + 20.0 мм – швидкісний режим 200 хв⁻¹ (25 м/с); кубовидного щебню крупністю -20.0 + 10.0 мм – відповідно 600-650 хв⁻¹ (70-80 м/с). Максимальний вміст кубовидних фракцій в класі крупності -20.0 + 10.0 мм 95% досягається при швидкості ротора 650-700 хв⁻¹ (швидкість вильоту 75-80 м/с). Максимальний вміст кубовидного щебню в класі -10.0 мм, а саме 94-95% досягається при швидкості розгінного ротора в межах 700-800 хв⁻¹ (швидкість вильоту 70-80 м/с). Одержані дані практично уможливлюють вибір раціонального швидкісного режиму роботи відцентрово-ударної дробарки для одержання максимального виходу кубовидного щебню.
Визначення раціональних режимних параметрів дроблення граніту для одержання кубовидного щебню
Keywords: granite; crushing; cubiform crushed stone; centrifugal-impact crusher; operating parameters; видобування нафти; граніт; дроблення; кубовидний щебінь; відцентрово-ударна дробарка; режимні параметри